188 Enhancing junior doctor leadership and management skills as innovation fellows. (16th November 2020) - Osanlou, Orod; Clark, Kate; Griffiths, Bethany; Morton, Michaela; Matoug, Muni; Gwenter, Ricia; Brown, Richard; Khan, Hafsa; Phillips, Carys
Abstract : Aims: The Site Innovation Lead at Wrexham Maelor Hospital, Betsi Cadwaladr University Health Board appointed 12 junior doctors as Innovation Fellows in order to enhance their leadership and management skills. Methods: Junior doctors competitively applied to be a Wrexham Innovation Fellow. This formal leadership position included mentoring from the Site Innovation Lead and quality improvement (QI) training. Each Innovation Fellow was guided and encouraged to undertake the Improving Quality Together' (IQT) Welsh QI Development Programme as well as the Edward Jenner NHS Leadership Academy Programme. Funding has also been secured to deliver further formal QI training from Improvement Cymru. These skills have then been used by the Innovation Fellows when undertaking QI and innovation work. Results: As of August 2020, 8/12 (75%) of Innovation fellows completed the Improving Quality Together Welsh QI Development Programme and 5/11 (45%) have completed the Edward Jenner NHS Leadership Academy Programme. 10/12 (83%) feel that their leadership skills have improved since becoming an Innovation Fellow. 11/12 (92%) feel more motivated to undertake QI and innovation since becoming an Innovation Fellow, and 10/12 (83%) feel more motivated to support others undertake QI and innovation since starting the programme. 10/11 (91%) also feel that their leadership experience may better equip them in the planning and management of future COVID challenges. Conclusions: Empowering junior doctors with leadership responsibilities while also providing mentorship and formal QI training can enhance their leadership skills, motivate them to undertake QI and innovation, and empower them to supervise and mentor others. Other NHS organisations should consider appointing Innovation Fellows in a similar way to Betsi Cadwaladr University Health Board.